Mulheres negras militantes na educação em Açailândia, Maranhão - SILVA, Cíntia Valéria de Souza (2023)
Practices We live in a structure sedimented by gender and racial oppression that affects the black population, especially women, who, since the schooling process, are silenced and affected by an educational policy that does not consider the racial agenda as a priority on the agenda. Faced with this reality, this work aims to understand the educational trajectory of black women and militants in the municipality of Açailândia, Maranhão, Brazil. The theoretical basis is preferably based on black authors, aiming to strengthen and give visibility to these literatures, so we have names such as: Ribeiro (2018), Hooks (2019), Gomes (2012), Davis (2018), Silva (2019). For that, we used the qualitative approach as methodology, with the oral history method and the research technique semi-structured interviews that were carried out with three black women. In view of the study, it was possible to infer that all life trajectories were, at some point, marked by the harmfulness of racism, demanding from these subjects a constant struggle for the realization of their rights. We believe that it is urgent to think about building an education project that recognizes and values black identities. However, as a product of this dissertation, we intend to create a podcast with the women's narratives, as we understand that this tool is an educational instrument that has the power to share stories, knowledge and, mainly, anti-racist actions in the educational context.